Find the general solution $u(x,y)$ to $$x u_x + y u_y = 0$$

Attempted solution - The characteristic equation satisfy the ODE $dy/dx = y/x$. To solve the ODE, we separate variables: $dy/y = dx/x$; hence $\ln(y) = \ln(x)- C$, so that $$y = x \exp(-C)$$

I am a bit confused in finding the general solution for $u(x,y)$. I just want to know if I am on the right track or not. I haven't taken a formal ODE course but I have self-studied but not in a while. Any suggestions would be greatly appreciated.

  • $\begingroup$ @Winther Not sure I thought that it was just a constant used. I was following an example from the PDE book by Strauss $\endgroup$ – Wolfy May 18 '17 at 23:13
  • $\begingroup$ I think you mean $u(x,y)$ not $u(x,t)$ $\endgroup$ – Rumplestillskin May 18 '17 at 23:13
  • $\begingroup$ @Rumplestillskin Yes, I believe so too must be an error I will change it. $\endgroup$ – Wolfy May 18 '17 at 23:15
  • 1
    $\begingroup$ You need to reread what the method of characteristics tell you to do. The characteristic equation is not correct. It should be $dy/dx = y/x$ which follows from $dy/($coefficient of $u_y$) = $dx/($ coefficient of $u_x$). $\endgroup$ – Winther May 18 '17 at 23:15
  • $\begingroup$ @Winther Could you tell me why $dy.dx = y/x$ $\endgroup$ – Wolfy May 18 '17 at 23:17

We consider first order PDE's as a first order directional derivative. That is suppose we parametrize a curve $(x,y)$ by a parameter $\xi$. So that

$$ u=u(x(\xi),y(\xi)) $$

$$ \frac{\mathrm{d}u}{\mathrm{d}\xi}=\frac{\mathrm{d}x}{\mathrm{d}\xi}\frac{\partial u}{\partial x}+\frac{\mathrm{d}y}{\mathrm{d}\xi}\frac{\partial u}{\partial y} $$

Comparing to your original PDE

$$ 0 = x\frac{\partial u}{\partial x}+y\frac{\partial u}{\partial y} $$

We then set

$$ \frac{\mathrm{d}u}{\mathrm{d}\xi}=0 $$

$$ \frac{\mathrm{d}x}{\mathrm{d}\xi}=x $$

$$ \frac{\mathrm{d}y}{\mathrm{d}\xi}=y $$

Along the characteristics $u$ is constant and

$$ \mathrm{d}\xi=\frac{\mathrm{d}x}{x}=\frac{\mathrm{d}y}{y} $$

Integrating we find that $y/x$ is also a constant. Since $u$ is a constant and $y/x$ is a constant, we are free to set one constant equal to an arbitrary function of the other constant.

$$ u(x,y)=\varphi(\frac{y}{x}) $$

where $\varphi$ is an arbitrary differentiable function.

  • $\begingroup$ I haven't taken much ODE so I'm a bit lost on why $d x/ d\Epsilon = x$? Could you clarify that? $\endgroup$ – Wolfy May 19 '17 at 1:35
  • $\begingroup$ You compare the original PDE to the directional derivative, equate coefficients. $\endgroup$ – Tucker May 19 '17 at 2:02
  • $\begingroup$ Do you know how I would proceed with this if we were asked to find the solution that satisfies the initial condition $u(x,y) = y$ whenever $x^2 + y^2 = 1$? $\endgroup$ – Wolfy May 19 '17 at 5:55
  • $\begingroup$ The boundary condition is addressed below. $\endgroup$ – Tucker May 19 '17 at 6:07


$$ u(x,y)=y $$

when $x^2+y^2=1$

Since $\varphi$ was arbitrary let me define $F$ so that $\varphi(z)=F(z^2)$, our general solution is then

$$ u(x,y)=F(\frac{y^2}{x^2}) $$

Let me know apply the boundary condition

$$ y=F(\frac{y^2}{1-y^2}) $$

Define $\zeta$ so that

$$ \zeta=\frac{y^2}{1-y^2} $$

$$ \zeta=y^2(1+\zeta) $$

$$ y=\sqrt{\frac{\zeta}{1+\zeta}} $$

so that

$$ F(\zeta)=\sqrt{\frac{\zeta}{1+\zeta}} $$

$$ u(x,y)=F(\frac{y^2}{x^2})=\sqrt{\frac{\frac{y^2}{x^2}}{1+\frac{y^2}{x^2}}} $$

$$ u(x,y)=\frac{y}{\sqrt{x^2+y^2}} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.